Supply ecosystems and the concept of resilience: A literature review - Christopher Münch; Emanuel Marx (Changing Tides: The New Role of Resilience and Sustainability in Logistics and Supply Chain Management – Innovative Approaches for the Shift to a New Era. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 33, 2022)
Purpose: Established approaches to supply chain management are increasingly being challenged due to disruptive events that neglect the dynamics and interdependencies of supply chains. Supply ecosystems form a new theoretical view of the supply chain that is more in line with systemic thinking, although it is unclear how these can contribute to increased resilience. Methodology: Based on the assumption that supply ecosystems are complex adaptive systems with a dynamic capacity to adapt to changes in an environment and evolve, we conducted a systematic literature review of 24 peer-reviewed journal articles. Findings: The review identifies the attributes of complex adaptive systems making them resilient and matches these with the concept of supply ecosystems. The resulting framework demonstrates how supply ecosystems contribute to increased resilience through the systemic nature. Originality: The paper extends research on supply ecosystems by conceptualizing them as complex adaptive systems and identifying attributes that can contribute to system resilience. Thus, the study contributes to the emerging research of supply ecosystems.
urn:nbn:de:gbv:830-882.0200518; hdl:10419/267179; https://econpapers.repec.org/RePEc:zbw:hiclpr:33
Keywords: 650; Advanced Manufacturing; Industry 4.0